Relationship lending in the interbank market and the price of liquidity - Falk Bräuning; Falko Fecht (Federal Reserve Bank of Boston, 2016)
We empirically investigate the effect that relationship lending has on the availability and pricing of interbank liquidity. Our analysis is based on a daily panel of unsecured overnight loans between 1,079 distinct German bank pairs from March 2006 to November 2007, a period that includes the 2007 liquidity crisis that marked the beginning of the 2007/08 global financial crisis. We find that (i) relationship lenders are more likely to provide liquidity to their closest borrowers, (ii) particularly opaque borrowers obtain liquidity at lower rates when borrowing from their relationship lenders, and (iii) during the crisis, relationship lenders provided cheaper loans to their closest borrowers. Our results hold after controlling for search frictions as well as a large set of (time-varying) bank and bank-pair control variables and fixed effects. While we find some indication that lending relationships help banks reduce search frictions in the over-the-counter interbank market, our results establish that bank-pair relationships have a significant impact on interbank credit availability and pricing due to mitigating uncertainty about counterparty credit quality.
Keywords: D61; E44; G10; G21; 330; interbank market; relationship lending; financial crisis; central counterparty; financial contagion